Nonlocal Modeling of Superelastic Behavior in Thin Plate with Central Hole Shape Memory Alloys Under Mechanical Loads - Mohammed Saad Qasim (Journal of Techniques)
Smart metallic materials known as Shape Memory Alloys, or SMAs, have unique deformation attributes, which consist of the shape memory effect as well as superelasticity. In this research, a non-local model of NiTi has been developed to illustrate small-volume SMAs' superelastic behavior. First, an exhaustive overview of the literature was conducted to observe the previous studies on the superelastic behavior of small-volume SMAs and the application of the nonlocal approach in material modeling. Next, a nonlocal model was developed through the Finite Element Method (FEM) to accurately simulate the superelastic effect of small-volume SMAs, accounting for their complicated microstructure and nonlocal effects. The model's accuracy was validated by comparing findings with data from experiments reported in published works. Lastly, the developed nonlocal model is used to study the effects of various parameters, such as the strain rate and the characteristic length scale, on the superelastic behavior of small-volume SMAs. One of the outcomes of this study is introducing a specific finite detail model in the Abaqus R software program, wherein the nonlocal variable works as an extra degree of freedom. This specimen may make the numerical simulation related to the small-volume SMAs' superelastic behavior possible. Additionally, the nonlocal model was validated by comparing its results with data from experiments reported in published works. Moreover, investigating various parameters using the nonlocal model will provide insights into the factors influencing the superelastic behavior of small-volume SMAs under mechanical loads.